REACTIVATION OF RELIEF AND FASTNESS OF THE ARTICLES ACTING FACES WITH THE HELP OF COMPOSITION DRESSINGS - V. E. Liventsev; V. N. Fedulov (Литьë и металлургия)
The ways of carrying out of the process with high-temperature (800 degrees Celsius and higher) heating and heating up to 600 degrees Celsius are offered. The evaluation of the testing results of the offered ways in the industrial conditions is carried out.